Approches critiques des technologies en éducation et implications didactiques - Simon Collin (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
At the crossroads of critical approaches in language education and technology in education, the study of technology in language education (eg, Warschauer, 1998; Ollivier, 2019) has complementary critical foundations to ensure its development, provided that a critical mass of researchers work to further structure them. To this end, we propose to focus on critical approaches to technology in education as contributory approaches to the critical study of technology in language education. To do so, we begin by establishing some markers of critical approaches in general. We then mobilize them for the case of technology in education, positioning them as ways to overcome two common conceptions of the "technology-education" relationship: instrumentalist and technodeterministic approaches. To provide a more tangible view of their contributions, we finally present a theoretical framework among others (see Collin, 2022), which apprehends technopedagogical innovation at the intersection of critical approaches to technology and Social Shaping of Technology (SST) studies.